Extrapolation and Uncertainty Evaluation of Carbon Dioxide and Methane Emissions in the Qinghai-Tibetan Plateau Wetlands Since the 1960s - Zhang, Jiang; Zhu, Qiuan; Yuan, Minshu; Liu, Xinwei; Chen, Huai; Peng, Changhui; Wang, Meng; Yang, Zhenan; Jiang, Lin; Zhao, Pengxiang (Frontiers in Earth Science, 2020)
Wetlands are important modulators of atmospheric greenhouse gas (GHGs) concentrations. However, little is known about the magnitudes and spatiotemporal patterns of GHG fluxes in wetlands on the Qinghai-Tibetan Plateau (QTP), the world’s largest and highest plateau. In this study, we measured soil temperature and the fluxes of carbon dioxide (CO2) and methane (CH4) in an alpine wetland on the QTP from April 2017 to April 2019 by the static chamber method, and from January 2017 to December 2017 by the eddy covariance (EC) method. The CO2 and CH4 emission measurements from both methods showed different relationships to soil temperature at different timescales (annual and seasonal). Based on such relationship patterns and soil temperature data (1960-2017), we extrapolated the CO2 and CH4 emissions of study site for the past 57 years: the mean CO2 emission rate was 1096.59 mg C m-2 h-1 on different measurement methods and timescales, with the range of the mean emission rate from 421.17 to 1754.99 mg C m-2 h-1, while the mean CH4 emission rate was 32.99 mg C m-2 h-1, with the ranges of the mean emission rate from 16.95 to 46.25 mg C m-2 h-1. The estimated regional CO2 and CH4 emissions from permanent wetlands on the QTP were 94.29 and 2.37 Tg C year-1, respectively. These results indicate that uncertainties caused by measuring method and timescale should be fully considered when extrapolating wetland GHG fluxes from local sites to the regional level. Moreover, the results of global warming potential showed that CO2 dominates the GHG balance of wetlands on the QTP.